Urgensi Peran Generasi Muda dalam Meningkatkan Pendidikan Berkualitas - Putri Tsania Azzahra; Masduki Asbari; Devina Evifa Nugroho (Journal of Information Systems and Management (JISMA), 2024)
The aim of this study is to find out how important the role of the younger generation is in improving quality education and what educators need to improve the quality of Indonesian education. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to the oral narrative from the Youtube channel @klasbersama entitled "AoC Talkshow Eps 2: The Role of the Young Generation in Improving Quality Education" presented by Wikan Sakarinto, ST, M.Sc, Ph.D as Director General of Vocational Education at the Ministry of Education, Culture, Research and Technology, and Galih Sulistyaningra S.Pd, M.A as founder of Bekal Pendidikan community and also ASN for the DKI Jakarta Provincial Government. The results of this study explain that the world continues to experience change and we must be able to adapt to these changes, teachers must change their mindset and change learning methods so that the lessons given are relevant to the problems they face every day.